Meet Katie at the beach - Johnson, Rebecca 1966- (Puffin Books, 2020)
Hi! I'm Katie. I have a wobbly tooth that won’t come out! But it’s not going to spoil my trip to the beach. We’re going to eat mangoes and play beach cricket!
Keywords: Beaches / Juvenile fiction; Australian fiction; Children's stories; Beaches; Children's stories, Australian; Fiction; Juvenile works